1-(2+w)=(w+5)

Simple and best practice solution for 1-(2+w)=(w+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-(2+w)=(w+5) equation:


Simplifying
1 + -1(2 + w) = (w + 5)
1 + (2 * -1 + w * -1) = (w + 5)
1 + (-2 + -1w) = (w + 5)

Combine like terms: 1 + -2 = -1
-1 + -1w = (w + 5)

Reorder the terms:
-1 + -1w = (5 + w)

Remove parenthesis around (5 + w)
-1 + -1w = 5 + w

Solving
-1 + -1w = 5 + w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-1w' to each side of the equation.
-1 + -1w + -1w = 5 + w + -1w

Combine like terms: -1w + -1w = -2w
-1 + -2w = 5 + w + -1w

Combine like terms: w + -1w = 0
-1 + -2w = 5 + 0
-1 + -2w = 5

Add '1' to each side of the equation.
-1 + 1 + -2w = 5 + 1

Combine like terms: -1 + 1 = 0
0 + -2w = 5 + 1
-2w = 5 + 1

Combine like terms: 5 + 1 = 6
-2w = 6

Divide each side by '-2'.
w = -3

Simplifying
w = -3

See similar equations:

| x-24=-10 | | -16.4/(-2) | | 4(x-2)3=4x+10 | | 3x+4-10=11(x-2)-x | | 2/5n=-16 | | x/15=4/10 | | 2x+5(2x+4)=80 | | 10+8+-10t+-6t-10t= | | -18=9+t | | 24-3(-1)=6-4y | | 0.0399x^2+2x-75=0 | | (x+1)(x-4)-6=0 | | 2/3k-12=30 | | X(-2x-4)=1 | | w^2+(2w+44)=46 | | 1+3x=-7-1x | | 2ln(x-5)=-2 | | 8n+15=15 | | -1(5x+2)=3 | | 2x=360-140 | | -11/36=-7/2x | | 14+x+26+x+12=x+23 | | 2(4+3x)+2(x)=38 | | 6-8x=-50 | | 0=x^2+22x+49 | | 2x=360+140 | | -3+6h+-2+-3+-4h= | | 5x+40=72 | | 12.50*n-50=200 | | C+87=97 | | x-64=26 | | 2n-9-5-2.4n+4= |

Equations solver categories